Basics of Functional Echocardiography in Children and Neonates - Tissot, Cécile; Muehlethaler, Vincent; Sekarski, Nicole (Frontiers in Pediatrics, 2017)
Echocardiography has become an invaluable tool in the pediatric and neonatal intensive care unit. “Point-of-care” or “target” or “focus” echocardiography allows bedside evaluation of the hemodynamic status of the patient, helps in directing treatment and thus improves patients care. In order to be able to perform “point-of-care” echocardiography, it is essential to understand the principles of ultrasound, to know the echocardiographic equipment and settings necessary to acquire the images. This article focuses therefore on the basics of cardiac ultrasound. It is meant to give a comprehensive overview of two-dimensional echocardiographic views, M- mode imaging and Doppler echocardiography for neonatologists and pediatric intensivists. It is richly illustrated for better understanding. Lastly we provide a summary of current clinical applications of target echocardiography in the intensive care setting.